Analysis of thermal hydraulic flow and heat transfer augmentation in dimpled tubes based on experimental and CFD investigations - Raad Al-Haidari, Saad; Mohammed, Ameer; Ramadhan Al-Obaidi, Ahmed (The International journal of heat and fluid flow, 2024)
•This research explores the use of ring dimples to improve the efficiency and heat transfer in the inner pipes of heat exchangers.•Spherical dimple rings are examined with various arrangements.•In this study, numerical simulations and experimental work are conducted to simulate the best geometric design of enhanced tubes for thermal-hydraulic performance.•Analysis of thermal-hydraulic flow and heat transfer augmentation in dimple ring tubes.•The simulations are validated with experimental data. This study investigates heat transfer enhancement in turbulent flows through dimpled tubes. The goal is to improve heat transfer efficiency in applications involving pipes. Numerical simulations were conducted to analyze heat transfer rate, friction factor, and performance for various dimpled pipe designs on the inner surface tubes to compare with smooth tubes and validate with experimental data. Water flow within the Reynolds number range of 4,000 to 15,000 was simulated using the Reynolds-Averaged Navier-Stokes (RANS) equations and the realizable k-ε turbulence model. Results showed increased heat transfer rates in dimpled tubes compared to smooth tubes but with a trade-off of higher pressure loss. Among the investigated designs, lower dimple diameters (3 mm) with a fixed pitch (10 mm) and three dimple numbers offered the best and highest performance evaluation factor (PEF) of 1.3 compared to the other models. The dimpled tube configuration demonstrated significant heat transfer enhancements compared to a smooth tube at a Reynolds number of 6,000. Depending on the number, diameter, and spacing of the dimple rings, heat transfer improvements ranged from 28 % to 34.5 % at PBDR, 33 % to 37 % at NODR, and from 29 % to 38 % at DR. However, this enhancement came with a notable increase in friction factor, exceeding 65 % compared to the smooth tube. Numerical simulations closely approximated the experimental data, although minor discrepancies were observed in heat transfer and pressure drop predictions, with errors around 6.7 % and 9.4 %, respectively.